Universities and the innovation society: social implications and communication challenges - Ribeiro, Paula Campos (2015)
The purpose of this article is to understand the role played by universities in the innovation society, the correlation of this in the communication models adopted universities. To reach this objective, we will promote the debate on innovation in companies and organizations, and on the concepts related to the third mission of universities: knowledge and technology transfer, diffusion, dissemination, valorization and communication of innovation. As a result, we will infer about the strategies and the communication models used by universities in innovation transfer to society. The methodology used in this study, combines documental analysis, on literature and public deliberations; and direct observation in research consortia. The results point out the evolution from a unidirectional communication model to a dialogic model of interorganizational collaboration and participation of universities in society, and a greater involvement and engagement in narrowing social relations. The originality of this study relates to the Organizational and Strategic Communication approach that was produced.